An empirical analysis of commercial bank's profitability determinants in Malaysia / Fatin Nadirah Mohamad Roslan - Mohamad Roslan, Fatin Nadirah (2016)
The main purpose of this research is to find out the profitability determinants of commercial banks in Malaysia. 5 commercial banks have been chosen to represent the commercial banks in Malaysia during the time line from 2004 till 2014. ROA was chosen as a dependent variable to estimate the commercial bank's profit, and 4 independent variables which are base lending rate, inflation rate, capital adequacy ratio, and bank size after running these data on the data analysis software, it is found that only base lending rate, size of bank, and capital adequacy ratio are significant variables while inflation rate is insignificant in determining the profitability determinants of commercial banks in Malaysia.